Cross-lagged analysis of burnout and insomnia in older adult patients with diabetes mellitus complicated by hypertension: a 1-year longitudinal follow-up study - Zhang, Bailing; Zhou, Fengfei; Qian, Weipeng; Yang, Qingqing (Frontiers in Public Health, 2025)
ObjectiveThe aim of this study is to investigate the longitudinal bidirectional relationship between disease management burnout and insomnia symptoms in older adult patients with diabetes mellitus complicated by hypertension.MethodsA prospective cohort study was conducted, involving 326 older adult patients from the Sixth People’s Hospital of Nantong City, enrolled between January 2023 and April 2025. The study utilized the Burnout in Disease Management Scale and the Insomnia Severity Index (ISI) to perform four-stage evaluations at baseline (T0), 3 months post-discharge (T1), 6 months post-discharge (T2), and 12 months post-discharge (T3). A cross-lagged structural equation model was employed to analyze the bidirectional relationship between burnout and insomnia, while accounting for confounding factors such as gender and comorbidities.ResultsThe influence of burnout on insomnia was significant, with burnout at T0 strongly predicting insomnia at T1 (β = 0.29, p < 0.001), and the predictive effect of burnout at T2 on insomnia at T3 peaking (β = 0.24, p < 0.001). Conversely, the impact of insomnia on burnout was also evident, with insomnia at T0 predicting burnout at T1 (β = 0.15, p < 0.05), insomnia at T1 predicting burnout at T2 (β = 0.19, p < 0.01), and insomnia at T2 predicting burnout at T3 (β = 0.21, p < 0.01). Additionally, a gender moderation effect was observed, with women exhibiting a higher degree of burnout at baseline (β = −0.11, p < 0.05), and the predictive effect of burnout at T2 on insomnia at T3 was more pronounced in women.ConclusionA significant bidirectional and vicious cycle relationship exists between disease management burnout and insomnia symptoms in older adult patients with diabetes and hypertension. Furthermore, T2 (6 months post-discharge) emerges as a critical window for intervention. It is recommended that gender-differentiated intervention strategies be implemented and that sleep management be integrated into the standardized diagnosis and treatment pathway for this patient population.